Agrarian Reform Community Development the Amihan experience - Dianala, Ma. Fideles B. (1995)
Agrarian reform community (ARC) development was the strategy adopted by the Department of Agrarian Reform in mid-1993 to effect a fairer and more meaningful implementation of the Comprehensive Agrarian Reform Program. It was later proclaimed by President Fidel V. Ramos as the key program for national development. Barangay Amihan is an ARC established in 1993. After two years, this study sought to find out the condition of the barangay basing on eight elements of viability. It also tried to identify significant factors in development so that appropriate recommendations could be presented. Considerable emphasis was devoted to the cooperative given the importance accorded to it in influencing the spread of development. This is mainly a descriptive study which utilized a combination of methodologies: focus group discussion, interviews with key informants, secondary data gathering and direct observation. The stdy discovered that some elements of viability were at best minimally present. It was also found that the agrarian problem, the Development Facilitator, the cooperative, the strategy and the implementing agency itself were significant factors in the whole process. As a transforming mechanism, the cooperative, with its low level of maturity, was unable to spur development. some recommendations are presented at the last portion covering action agenda, policy changes and suggestions for future study.
Research Paper (RDM 299). -- Iloilo City : UPV-CM, October 18, 1995.